INFORMATION DIFFERENCES OF CORATAL ANATOMI MAGNETIC RESONANCE IMAGE ANTHOMY MAGNETIC RESONANCE (MRCP) IN T2 FRFSE (FAST RECOVERY FAST SPIN ECHO) SELECTION BETWEEN USE OF ARC WITH NO ARC - Yeti Kartikasari; Jeffry Ardiyanto; Ary Lasminar Firdani (Jurnal Imejing Diagnostik (JImeD), 2018)
Background : MRCP is a biliary tract and pancreatic duct imaging technique, one technique that uses a breath hold. The technique speeds up acquisition time by using the Parallel Imaging ARC method so that it reduces the encoding phase on K-Space to reduce breath hold. Therefore it can increase image sharpness and reduce blurring image. The purpose of this study was to determine the differences in anatomical image information between using ARC and without using ARC on MRCP examination of coronal T2 FRFSE sequence pieces and to find better anatomical image information between using ARC and without using ARC on MRCP examination of FRFSE T2 sequences.Method : The type of research conducted by the author is quantitative research with an experimental approach. This research was carried out with 1.5 T MRI at Santo Borromeus Hospital, Bandung. Data in the form of 16 MRCP anatomical images of coronal chunks of T2 FRFSE sequences from 8 patients using ARC and without using ARC. Scores on the image are carried out in the gallbladder, cystic duct, common hepatic duct, intra-hepatic duct, common bile duct and pancreatic duct using questionnaires to 3 radiology specialists (respondents). The results of the respondents were analyzed using Wilcoxon statistical test to find out the differences in MRCP anatomical information on FR2E T2 sequences between using ARC and without using ARC and to find better anatomical image information from the two sequences seen from the mean rank value.Result : The results showed that there were significant differences in MRCP anatomical image information of coronal T2 FRFSE sequences between the use of ARC and without using ARC with a significance value of 0.05. Based on mean rank results, MRCP information on T2 FRFSE sequence coronal pieces using ARC has a mean rank value of 4.50 while MRCP T2 FRFSE coronal sequence sequences using without ARC have a mean rank value of 0.00, meaning FRFSE T2 sequences using ARC have better image information than FRFSE T2 without using ARC.Conclusion : Suggestion, the parallel imaging technique of the ARC method was applied on the MRCP examination of T2 FRFSE sequences and the data from this study could be used as baseline data to add ARC as the operational standard of the MRCP examination procedure.